Collective Expression of Persipa Pati Football Supporters Fanaticm Through the “Diurus Cah-Cah” Movement - Mareno Andrian Winanda; Mugiyo Hartono (Universitas Negeri Semarang, 2026)
This study examines the collective expression of fanaticism of Persipa Pati supporters through the